(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
This research aims to measure and analyze the economic determinants facing foreign direct investment in Iraq, notably the macroeconomic variables, and variables of monetary and fiscal policy and external balance, in order to provide initial idea can help the investment decision maker to reach a map of the policies that can be followed to attract flows of direct foreign investment. The research was diagnosed variables, which have a positive effect on foreign direct investment flows (attraction factors), which are according to their importance : the interest rate, money supply, government expenditures, exchange rate GDP, and credit size, as well as it was determined the variables, which have a negative impact, i.e., political unrest, corruption, legal, administrative and institutional restrictions, in addition to the inflation, the budget deficit, external resources gap, economic exposure, and the